A STUDY ON DIRECT AND INDIRECT SPEECH ACTS IN CARTOON SPONGEBOB SQUAREPANTS ENTITLED “PRE-HIBERNATION WEEK” - KRISTIANA, DHIYAS RIZKI (Jurnal Ilmiah Mahasiswa FIB, 2013)
There are two problems of the study: (1) what are the locutions and illocutions found in the dialogues containing speech acts between two main characters of Spongebob Squarepants cartoon film in the episode of “Pre-hibernation Week”? and (2) What are the types of speech acts found in the dialogues between the two main characters according to their structural forms and communicative functions? Qualitative approach and document analysis are applied in this study. While, the data source is dialogues between SpongeBob and Sandy of Spongebob Squarepants cartoon film entitled “Pre-hibernation week” and the data are the speech acts expressions uttered by the characters.. The results of this study shows that there are 59 declaratives, 51 imperatives and 22 interrogatives type of locution in 132 utterances. The researcher also found 80 direct speech acts and 52 indirect speech acts by using speech act theories proposed by Searle (1976) and Grundy (2000). The researcher suggests the next researcher learn more other linguistic subjects and analyze other objects to enrich the information related to linguistic phenomena.     Keyword: pragmatics, speech act, direct and indirect speech act.